Altered states : sex, nation, drugs, and self-transformation in Victorian spiritualism - Tromp, Marlene, 1966- (Albany : State University of New York Press, 2006)
Altered States examines the rise of Spiritualism--the religion of séances, mediums, and ghostly encounters--in the Victorian period and the role it played in undermining both traditional female roles and the rhetoric of imperialism. Focusing on a particular kind of séance event--the full-form materialization--and the bodies of the young, female mediums who performed it, Marlene Tromp argues that in the altered state of the séance new ways of understanding identity and relationships became possible. This not only demonstrably shaped the thinking of the Spiritualists, but also the popular consciousness of the period. In diaries, letters, newspaper accounts, scientific reports, and popular fiction, Tromp uncovers evidence that the radical views presented in the faith permeated and influenced mainstream Victorian thought.
Spirited sexuality : sex, marriage, and Victorian spiritualism -- Wedding stories/ghost stories -- Ghostly erotics and the imperialism in the Victorian drawing room -- Economics, race, and the specter of class -- Drunk with power : stories of ghostly others -- Under the influence : the fox sisters and pernicious spirits -- Haunted : Elizabeth d'Espérance, social justice, and the evolution of mediumship.
Includes bibliographical references (pages 213-223) and index.
Print version record.
English.
JSTOR
Keywords: Spiritualism -- England; England -- Religion -- History -- 19th century; England -- Religion -- 19th century; Spiritisme -- Angleterre; Angleterre -- Religion -- 19e siècle.; BODY, MIND & SPIRIT -- Spiritualism; Religion; Spiritualism; England; Spiritismus; Identität; Sexualität; Großbritannien; Frau; 1800-1899; History